2020
DOI: 10.1111/jora.12552
|View full text |Cite
|
Sign up to set email alerts
|

Puberty and Transdiagnostic Risks for Mental Health

Abstract: Puberty in girls represents a notable period of vulnerability for different psychological disorders. The research literature has primarily considered external and contextual factors that might explain these rises in symptomatology. In the present study, we investigate relations of pubertal status and timing with individual cognitive, emotional, and behavioral tendencies, commonly identified as transdiagnostic processes, in a sample of N = 228 girls (Mage = 11.75 years). We also test whether these transdiagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 81 publications
2
20
0
Order By: Relevance
“…Given the shared perseverative focus of rumination and co‐rumination, I expected the constructs to be related. Indeed, studies of youth from middle childhood to middle adolescence indicate significant relations between rumination and co‐rumination (Felton et al., 2019; Jose et al., 2012; Mendle et al., 2020; Rose, 2002; Stone & Gibb, 2015). These effects typically are small to moderate ( r s about .25–.45).…”
Section: What Does It Mean To Co‐ruminate?mentioning
confidence: 99%
“…Given the shared perseverative focus of rumination and co‐rumination, I expected the constructs to be related. Indeed, studies of youth from middle childhood to middle adolescence indicate significant relations between rumination and co‐rumination (Felton et al., 2019; Jose et al., 2012; Mendle et al., 2020; Rose, 2002; Stone & Gibb, 2015). These effects typically are small to moderate ( r s about .25–.45).…”
Section: What Does It Mean To Co‐ruminate?mentioning
confidence: 99%
“…However, results from Vannucci et al (2014) and Vetter et al (2013), as well as part of the results from Mendle et al (2020), showed no pubertal effects on three of such measures. Chaku and Hoyt (2019) conducted a seven year-long longitudinal study assessing participants Tanner stages and self-control (using a subscale of the Social Skills Rating System) at exactly the same ages, thus controlling for age differences in the design of the study.…”
Section: Imentioning
confidence: 79%
“…Among these, there were two publications reporting the same results on the same sample: a paper (Herlitz et al, 2013) and a dissertation (Lovén, 2012). Two other studies, Koch et al (2020) and Mendle et al (2020), seem to have used the same sample, but they report results from different measures. Thus, we had a total of 27 reports, based on 26 studies and involving 25 datasets, included in the review.…”
Section: Search Results and Study Selection And Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has documented the linkage between early puberty and undesirable developmental outcomes, such as depressive symptoms, delinquency, and substance use among adolescent girls (Beltz, et al, 2020;Negriff, et al, 2011;Mendle, et al, 2020). These effects may hold concurrently and prospectively over time during adolescence (Graber, 2013) and even persist well in adulthood (Tsai, et al, 2014).…”
mentioning
confidence: 99%